2016
DOI: 10.1371/journal.pone.0161508
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Virulent Porcine Epidemic Diarrhea Virus Proliferation by the PI3K/Akt/GSK-3α/β Pathway

Abstract: Porcine epidemic diarrhea virus (PEDV) has recently caused high mortality in suckling piglets with subsequent large economic losses to the swine industry. Many intracellular signaling pathways, including the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, are activated by viral infection. The PI3K/Akt pathway is an important cellular pathway that has been shown to be required for virus replication. In the present study, we found that the PEDV JS-2013 strain activated Akt in Vero cells at early (5–15 min) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 53 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…We screened potential proteins for their ability to inhibit PEDV replication using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). Vero cells were collected and assayed after infection with PEDV (strain JS-2013) at an MOI (multiplicity of infection) of 1, as previously described [43]. We found that an IFN-inducible restriction factor, BST2, was upregulated in Vero cells during PEDV infection.…”
Section: Pedv Infection Upregulates the Expression Of Bst2 In Vero Anmentioning
confidence: 91%
See 1 more Smart Citation
“…We screened potential proteins for their ability to inhibit PEDV replication using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). Vero cells were collected and assayed after infection with PEDV (strain JS-2013) at an MOI (multiplicity of infection) of 1, as previously described [43]. We found that an IFN-inducible restriction factor, BST2, was upregulated in Vero cells during PEDV infection.…”
Section: Pedv Infection Upregulates the Expression Of Bst2 In Vero Anmentioning
confidence: 91%
“…Cells grown to 50%-60% confluence were transfected with siRNA using Lipofectamine RNAiMAX (Invitrogen, 13,778,150), according to the manufacturer's instructions. The PEDV variant strain JS-2013 was isolated and stored in our laboratory [43]. According to the requirements of different experiments, Vero cells were infected with PEDV at an MOI of 1 or 0.01, or were mock infected with DMEM.…”
Section: Antibodies Reagents and Plasmidsmentioning
confidence: 99%
“…To analyze the anti-sera or antibodies specificity interacted with PEDV, Vero cells were infected with PEDV (multiplicity of infection, MOI = 1), or mock infected with the medium, and then incubated for indicated times as previously described [16]. The cells were harvested and lysed using RIPA lysis buffer (Thermo, USA) containing protease inhibitor cocktail (Bimake, USA) and phosphatase inhibitor cocktail (Bimake, USA) on ice for 5 min.…”
Section: Virus Infection and Western Blot Analysismentioning
confidence: 99%
“…In addition, an increasing number of studies have demonstrated that viruses encode defensive mechanisms to evade the antiviral activities of host cells (Xing et al, 2013;Yang et al, 2018). However, hosts have many mechanisms aimed at detecting and disrupting PEDV replication and spread (Cao et al, 2015;Kong et al, 2016). An improved understanding of how this pathogen interacts with the host immune system is required to enhance efforts to control PEDV spread and to develop efficacious PEDV vaccines.…”
Section: Introductionmentioning
confidence: 99%